2015
DOI: 10.1208/s12249-015-0321-1
|View full text |Cite
|
Sign up to set email alerts
|

Biophysics and Thermodynamics: The Scientific Building Blocks of Bio-inspired Drug Delivery Nano Systems

Abstract: Abstract. Biophysics and thermodynamics are considered as the scientific milestones for investigating the properties of materials. The relationship between the changes of temperature with the biophysical variables of biomaterials is important in the process of the development of drug delivery systems. Biophysics is a challenge sector of physics and should be used complementary with the biochemistry in order to discover new and promising technological platforms (i.e., drug delivery systems) and to disclose the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…19,20 Its mode of action is explained by biophysics and thermodynamics approaches, that is, the degree of hydration, as based on the degree of hydration to provide protein protection and stable mechanical support. 29-31 Importantly, while hydrationis necessary for wound healing, degree of protein hydration is associated with their function and chemical stability. 29-31 Indeed, excess protein hydration, which is related to times and duration of their exposure to water (twice per week), impairs their integrity and functionality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 Its mode of action is explained by biophysics and thermodynamics approaches, that is, the degree of hydration, as based on the degree of hydration to provide protein protection and stable mechanical support. 29-31 Importantly, while hydrationis necessary for wound healing, degree of protein hydration is associated with their function and chemical stability. 29-31 Indeed, excess protein hydration, which is related to times and duration of their exposure to water (twice per week), impairs their integrity and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…29-31 Importantly, while hydrationis necessary for wound healing, degree of protein hydration is associated with their function and chemical stability. 29-31 Indeed, excess protein hydration, which is related to times and duration of their exposure to water (twice per week), impairs their integrity and functionality. 20-22,29-31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the antimicrobial activity of nanoencapsulated EO is enhanced due to its increase in solubility in aqueous phase. Moreover, it acts as a reservoir for bioactive compound which is released gradually over a prolonged time period [13].…”
Section: Introductionmentioning
confidence: 99%
“…Current liposomology is a huge and still progressing area. Liposomes belong to colloidal dispersion systems and are characterized as lyotropic liquid crystals (Demetzos 2008;2015). These particular liposomal lyotropic states are responsible for the mesophases taking place in phase transitions and are related to their thermal stress during phase transitions (Demetzos 2008;2015;Pippa et al, 2015).Liposomes are clinically used delivery systems with many advantages such as biocompatibility and biodegradability (Allen and Cullis, 2013).…”
Section: Introductionmentioning
confidence: 99%